2014
DOI: 10.1038/srep05783
|View full text |Cite
|
Sign up to set email alerts
|

The rice endophyte Harpophora oryzae genome reveals evolution from a pathogen to a mutualistic endophyte

Abstract: The fungus Harpophora oryzae is a close relative of the pathogen Magnaporthe oryzae and a beneficial endosymbiont of wild rice. Here, we show that H. oryzae evolved from a pathogenic ancestor. The overall genomic structures of H. and M. oryzae were found to be similar. However, during interactions with rice, the expression of 11.7% of all genes showed opposing trends in the two fungi, suggesting differences in gene regulation. Moreover, infection patterns, triggering of host defense responses, signal transduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
96
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(102 citation statements)
references
References 69 publications
6
96
0
Order By: Relevance
“…For example, future gains in understanding plant-microbe interactions might come from molecular comparisons of plant pathogens versus endophytes with regards to redox balance. For example, functional comparisons of the endophyte, Harpophora oryzae (Xu et al, 2014;Yuan et al, 2010), with its pathogenic relative, M. oryzae, might unpack differences in how Molina and Kahmann (2007) metabolism, nutrient signaling, growth, and antioxidation are connected in two fungi with opposing lifestyles. The importance and interconnectivity of host and pathogen ROS metabolism is becoming evident, but molecular understanding of the underlying mechanisms are still lacking.…”
Section: Summary and Future Issuesmentioning
confidence: 99%
“…For example, future gains in understanding plant-microbe interactions might come from molecular comparisons of plant pathogens versus endophytes with regards to redox balance. For example, functional comparisons of the endophyte, Harpophora oryzae (Xu et al, 2014;Yuan et al, 2010), with its pathogenic relative, M. oryzae, might unpack differences in how Molina and Kahmann (2007) metabolism, nutrient signaling, growth, and antioxidation are connected in two fungi with opposing lifestyles. The importance and interconnectivity of host and pathogen ROS metabolism is becoming evident, but molecular understanding of the underlying mechanisms are still lacking.…”
Section: Summary and Future Issuesmentioning
confidence: 99%
“…This indicated that the functional features of the secreted proteins in the Burkholderia species are most likely species-specific rather than lifestyle-specific, and thus would lead to distinct characteristics in their communication process with the host cells. Another study also demonstrated that although virulent microorganisms and endophytes seem to possess genetically similar weaponry, their expression and regulatory mechanisms are different (Lòpez-Fernàndez et al, 2015; Xu et al, 2014). Further studies of the expressions of specific proteins in each species and their interactions during communication with host cells might explain the differences between these pathogenic and mutualistic bacteria (Lòpez-Fernàndez et al, 2015; Seo et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Beneficial bacteria and fungi also indirectly protect hosts by increasing local and/or systemic pathogen resistance (Van Wees et al ., 2008; Pieterse et al ., 2014; de Lamo & Takken, 2020). The endophytic ascomycete fungus Harpophora oryzae confers local and systemic rice resistance to rice blast fungi ( Magnaporthe oryzae ) (Xu et al ., 2014). The basidiomycete Serendipita indica (formerly known as Piriformospora indica ) induces systemic resistance in Arabidopsis thaliana against biotrophic powdery mildew, through the phytohormone jasmonic acid (JA) (Stein et al ., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…High relatedness between beneficial and pathogenic species seems to be widespread, rather than exceptional, in plant-inhabiting fungi (Rodriguez et al ., 2009). Pathogenic species/strains are often found, without displaying virulence, in microbial communities on apparently healthy plants (García et al ., 2012; Xu et al ., 2014). In Arabidopsis thaliana , root-inhabiting bacteria may contribute to asymptomatic accommodation of filamentous microbial eukaryotes, by antagonizing their negative impacts on the host (Duran et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%